2022
DOI: 10.1001/jamanetworkopen.2022.0902
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Alcohol Consumption and Smoking With Disease Risk and Neurodegeneration in Individuals With Multiple Sclerosis in the United Kingdom

Abstract: IMPORTANCEUnderstanding the effects of modifiable risk factors on risk for multiple sclerosis (MS) and associated neurodegeneration is important to guide clinical counseling. OBJECTIVE To investigate associations of alcohol use, smoking, and obesity with odds of MS diagnosis and macular ganglion cell layer and inner plexiform layer (mGCIPL) thickness. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study analyzed data from the community-based UK Biobank study on health behaviors and retinal thickness (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…It is known that exposure to alcohol and cigarettes (tobacco smoke) results in tissue injury associated with oxidative stress [ 35 ]. It has been suggested that e-Cig could also produce similar effects [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that exposure to alcohol and cigarettes (tobacco smoke) results in tissue injury associated with oxidative stress [ 35 ]. It has been suggested that e-Cig could also produce similar effects [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…15 Continuous variables included MS-GRS (standardised for 545 individuals with undifferentiated ON), and Body Mass Index (kg/m 2 , UK Biobank Data-Field 21001). 15,[17][18][19] Categorical variables included smoking status (ever vs never vs missing, Data-Field 20160), [21][22][23] country of birth (England, Scotland, Northern Ireland, Republic of Ireland, Wales and Other/Unknown, Data-Field 1647), Townsend deprivation index quintiles (1 to 5 or missing, Data-Field 189), 37 and serum 25-OH vitamin D level at UKBB baseline assessment (su cient [>50nmol/L],…”
Section: Discussionmentioning
confidence: 99%
“…46 We did not nd signi cant association with additional clinical risk factors including BMI, smoking status, or vitamin D insu ciency at UKBB study entry, which have been highlighted in other studies. [15][16][17][18][19][21][22][23] It is possible that this is because our study only measures these variables at a single time point (UK biobank study entry) unrelated to diagnosis of ON and/or MS . Additionally, risk factors that are signi cant associated with disease in large observational epidemiology studies, sometimes do not explain enough variation in disease development to be useful for clinical prediction.…”
Section: Comparison To Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The same null causal effect was found for alcohol consumption despite observational studies revealing an involvement of it in MS risk, although with controversial findings. An association between moderate alcohol consumption and a lower odds of having MS was indeed found in some studies (Andersen et al, 2019;Hedström et al, 2014;Kleerekooper et al, 2022;Weiland et al, 2014), but an increased risk has been reported as well (Abdollahpour et al, 2018;Pakpoor et al, 2014). No evidence of association between alcohol consumption and MS risk has instead been found in a recent study (Dreyer-Alster et al, 2022).…”
Section: Genes and Gene Expressionmentioning
confidence: 91%